2016
DOI: 10.1002/2016gl069782
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the submesoscale energy cascade in the Alboran Sea thermocline from spectral analysis of high‐resolution MCS data

Abstract: Part of the kinetic energy that maintains ocean circulation cascades down to small scales until it is dissipated through mixing. While most steps of this downward energy cascade are well understood, an observational gap exists at horizontal scales of 103–101 m that prevents characterizing a key step in the chain: the transition from anisotropic internal wave motions to isotropic turbulence. Here we show that this observational gap can be covered using high‐resolution multichannel seismic (HR‐MCS) data. Spectra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 40 publications
1
14
1
Order By: Relevance
“…Measurements in the open ocean have found a consistent shape of the frequency and wave number spectra of internal waves (Garrett & Munk, ). Wave‐wave interaction is assumed to transfer energy from long wave lengths and periods to shorter ones until they become unstable and break (Müller et al, ; Sallarès et al, ; Thorpe, ), ultimately contributing to diapycnal mixing in the form of small‐scale turbulence. Seismic reflection data have been shown to be a useful tool to observe the vertical undulations of internal gravity waves and to derive spectra of their strength (Holbrook & Fer, ).…”
Section: Discussioncontrasting
confidence: 99%
“…Measurements in the open ocean have found a consistent shape of the frequency and wave number spectra of internal waves (Garrett & Munk, ). Wave‐wave interaction is assumed to transfer energy from long wave lengths and periods to shorter ones until they become unstable and break (Müller et al, ; Sallarès et al, ; Thorpe, ), ultimately contributing to diapycnal mixing in the form of small‐scale turbulence. Seismic reflection data have been shown to be a useful tool to observe the vertical undulations of internal gravity waves and to derive spectra of their strength (Holbrook & Fer, ).…”
Section: Discussioncontrasting
confidence: 99%
“…It must be noted that conventional, probe‐based oceanographic measures have an observational gap at horizontal scales of 10 3 m to 10 1 m [e.g., Müller et al ., ]. The availability of an observational system providing information on the variability of physical parameters within this range of scales should help to understand the physical processes that control the transition from anisotropic internal wave motions to isotropic turbulence, which at present are only partially observed in the ocean and poorly understood [e.g., Ferrari and Wunsch , ; Sallarès et al , ].…”
Section: Resultsmentioning
confidence: 99%
“…Most SO works performed to date have focused on processing the MCS data in order to create 2‐D acoustic reflectivity maps of the thermohaline boundaries, and their interpretation is based on the direct or spectral analysis of the resulting acoustic reflectivity maps. Together, these studies have demonstrated the potential of MCS data to image various structures of oceanographic interest [e.g., Biescas et al ., ; Buffett et al ., ; Eakin et al ., ; Sheen et al ., ] and to provide information on internal wave dynamics and turbulence with unprecedented lateral detail [e.g., Holbrook and Fer , ; Sheen et al ., ; Krahmann et al ., ; Sallarès et al , ]. Additionally, the fact that MCS acquisition has been widely used for academic, and oil exploration geological studies for the past 50 years, makes that a large volume of potentially available data exists in most parts of the World's oceans that are still unexploited for oceanographic purposes.…”
Section: Introductionmentioning
confidence: 99%
“…KH instability can be developed in stratified shear flows, where the shear is strong enough or the stratification is weak enough to bring the Richardson number ( Ri, the ratio of the squared buoyancy frequency N2 to the squared vertical shear S2 of the horizontal flow) below a critical value (Smyth & Moum, ). Sallares et al () first statistically predicted KH instability using the wave spectral analysis method based on seismic data. Here the KH billows induced by an energetic NIW are directly observed using the seismic method for the first time.…”
Section: Discussionmentioning
confidence: 99%